Power Take-Off Design, Integration and Commissioning of an Instrumented Open-Source Tidal Energy Converter (OSTEC) Testbed (Proceedings of the European Wave and Tidal Energy Conference, 2025)
The Open-Source Tidal Energy Converter (OSTEC), developed jointly between UNH-AMEC, SNL, NREL, and PNNL, will serve as a versatile testbed for open-source research and development (R&D) on many aspects of tidal energy research. Featuring a 2.5-meter diameter rotor plane, this tidal turbine is designed to generate publicly accessible datasets on power performance, mechanical and design loads, and tidal inflow conditions, all at Reynolds number scales for alternative off-grid market applications that enable upscaling of dynamic load response and power performance to utility grid scale markets. The primary objective  of OSTEC project is to design, build, and deploy  an instrumented marine turbine system in a real-world tidal environment. Hydrokinetic energy of tidal currents is captured by the turbine’s rotor and converted into mechanical power, which is transferred via the drivetrain (i.e., gearbox and generator) to the power take-off (PTO) system for electrical conversion.The focus herein is on the PTO subsystem, including the driveshaft, gearbox, motor-generator, control, and cooling system. The turbine’s most critical performance characteristics for PTO design and specification are speed and torque at the drive shaft. Once the required speed and torque range were established, PTO component selection and conceptual design were evaluated using a Pugh chart. The chosen generator for the OSTEC turbine is a Siemens SIMOTICS permanent magnet servo, rated at 26.2 kW. To match the turbine’s projected performance envelope, this generator requires a gearbox with a 20:1 ratio. To meet balance quality standards, unbalance from asymmetric sensor payloads in the rotor hub must be quantified and mitigated.A liftable rack houses the power electronics, PTO controls, voltage and current transducers, integrated into a UNH-adapted NREL Modular Ocean Data Acquisition (MODAQ) system. MODAQ records nacelle temperature, torque, and speed data from a multi-axis load cell and backup encoder, tested during integration. The SIMOTICS S120 drive control is programmed using Siemens Starter software for initial commissioning of the servo on a test stand using speed control. Torque control is omitted from lab tests due to the absence of turbine load and risk of component damage. Testing and modifications of the torque control scheme are deferred until deployment, during which OSTEC’s in-water checks and calibrations will be conducted.A ramp function is used to control the acceleration and deceleration of the motor, tailored to the maximum speed and characteristics of the OSTEC turbine. Startup and shutdown procedures were developed during PTO commissioning and laboratory tests. The emergency shutdown process is categorized into two cases: fast shutdown and true emergency shutdown. The true emergency shutdown, intended for life-or-death situations, involves engaging the generator’s internal magnetic holding brake, which could potentially harm the machine.A cooling system using ocean water regulates heat dissipation. Dry testing of turbine before deployment ensures seamless integration of instruments and controls, with performance and thermal characteristics monitored under incremental component loads.PTO design, assembly and component/sensor integration requires planning, a methodical workflow, compliance with standards. This presentation provides an overview of the OSTEC PTO subsystem’s development, from conceptual design to integration and commissioning.